Characterization of Meloidogyne enterolobii intercepted from baobab (Adansonia digitata L.) seedlings from Thailand during Japanese import plant quarantine inspection - Sekimoto S.; Inaba T. (Helminthologia, 2023)
In April 2019, baobab (Adansonia digitata L.) seedlings from Thailand, exhibiting galls on the roots, were intercepted during an import plant quarantine inspection at Chubu Centrair International Airport, Japan. Root-knot nematodes (RKNs) were extracted from the galled roots of baobab seedlings and identified by morphological, morphometrical and molecular methods as the guava root-knot nematode, Meloidogyne enterolobii Yang & Eisenback. The morphology and morphometrics of the intercepted population were similar to those of the original and subsequent descriptions of M. enterolobii. The sequences of D2–D3 of 28S rRNA, mtDNA intergenic COII-16S rRNA and COI genes obtained in this study matched well (99–100% similarity) with each of the gene sequences of M. enterolobii deposited in GenBank. Phylogenetic analysis of these genes revealed that the intercepted population clustered with M. enterolobii and clearly differed from other RKN species. To the best of our knowledge, this is the first report of M. enterolobii from baobab.